КОНУССИМОН УЗАТМАЛАРНИ ЛОЙИҲАЛАШДА НАЗАРИЯ ВА АМАЛИЁТ УЙҒУНЛИГИ МУАММОЛАРИ - Каримов, Б.Т. (SCIENCE and SOCIETY, 2020)
The article outlines the relevance of obtaining innovative results in the design of bevel gears, ensuring the consistency of theory and practice in the process of training qualified, competitive personnel.